Mechanism Design for Robotics Proceedings of the 4th IFToMM Symposium on Mechanism Design for Robotics - Gasparetto, Alessandro; Ceccarelli, Marco (Mechanisms and Machine Science,, 2019)
This volume contains the Proceedings of the 4th IFToMM Symposium on Mechanism Design for Robotics, held in Udine, Italy, 11-13 September, 2018. It includes recent advances in the design of mechanisms and their robotic applications. It treats, among others, the following topics: mechanism design, mechanics of robots, parallel manipulators, actuators and their control, linkage and industrial manipulators, innovative mechanisms/robots and their applications. This book can be used by students, researchers and engineers in the relevant areas of mechanisms, machines and robotics. .